2015
DOI: 10.1159/000381858
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NOX in the Regulation of Renal Tubular Expression of Na/K-ATPase in Acute Unilateral Ureteral Obstruction Rats

Abstract: Background/Aims: Renal tubular expression of Na/K-ATPase has been reported to be rapidly reduced in kidneys after unilateral ureteral obstruction (UUO), contributing to compromised sodium regulation. In this study, apocynin was utilized to test the hypothesis that the renal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) system is involved in the regulation of Na/K-ATPase expression in early UUO. Methods: Eighty Wistar rats underwent UUO or sham surgery, and half of each group was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Aquaporin1 is the major water channel in renal proximal tubule and loop of Henle that is responsible for reabsorbing 80% of glomerular filtrate [75, 76]. It has been reported that renal and cardiac AQP1 expressions were downregulated in conditions such as renal fibrosis in mice [77] and HS-induced HPN [78]. The present result is in accordance with the finding by Penna et al [79] who showed that 8% HS downregulated APQ1.…”
Section: Discussionsupporting
confidence: 91%
“…Aquaporin1 is the major water channel in renal proximal tubule and loop of Henle that is responsible for reabsorbing 80% of glomerular filtrate [75, 76]. It has been reported that renal and cardiac AQP1 expressions were downregulated in conditions such as renal fibrosis in mice [77] and HS-induced HPN [78]. The present result is in accordance with the finding by Penna et al [79] who showed that 8% HS downregulated APQ1.…”
Section: Discussionsupporting
confidence: 91%
“…Dysfunctional mitochondria in case of renal fibrosis led to depletion of ATP and eventually suppression of Na + /K + ATPase 35 . Furthermore, it has been reported that renal tubular expression of Na/K-ATPase rapidly decreased in kidneys after UUO, contributing to compromised sodium regulation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by the observation that significantly decreased renal AQP1 content was observed in the obstructed kidneys of rats with unilateral ureteral obstruction, suggesting that downregulation of AQP1 might be associated with tubule-interstitial fibrosis. 9 Moreover, in the mouse model of hypertension induced by a high-salt diet, the reduction of cardiac AQP1 might be associated with hypertension and cardiac injury, because angiotensin-receptor blocker treatment (valsartan) partially reversed the effects of a high-salt diet on hypertension with cardiac damage (fibrosis and inflammatory cell infiltration) and normalised cardiac AQP1 expression. 10 …”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that AQP1 expression is upregulated in the kidneys 7 and brain 8 of spontaneously hypertensive rats. 7 , 8 In contrast, recent studies reported that renal and cardiac AQP1 expression was downregulated and associated with renal fibrosis 9 and high-salt diet-induced hypertension. 10 Thus, it remains unclear whether AQP1 expression can directly or indirectly affect blood pressure and kidney injury.…”
Section: Introductionmentioning
confidence: 97%